FAKTOR-FAKTOR YANG MEMENGARUHI KEPUASAN KONSUMEN DALAM MENGONSUMSI PRODUK MINUMAN BIONAS - Lara, Dini; Alfikri; Sillia, Nova (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
. Bionas drinks are a new product on the market so it is important to identify consumer satisfaction. This research was conducted to analyze the demographic characteristics of consumers of Bionas products and the influence of consumer satisfaction factors in consuming Bionas probiotic drinks. This research was conducted from February to March 2024 using quantitative data from 105 respondents taken by purposive sampling. Respondents were selected from consumers who had consumed Bionas drinks. Data was obtained through a questionnaire and analyzed using the classic assumption test, multiple linear regression. The results of consumer demographic research state that women (63%), aged 17–27 years (59%), and most are students (49%). Most consumers have an income of less than IDR 1,000,000 per month (72%). Statistical analysis shows that the relationship between the independent and dependent variabels is very strong (R = 92.3%). R2 of 84.4% of the variation in consumer satisfaction can be explained by these variabels, while the remaining 15.6% is influenced by other factors not discussed in this research. The F test shows that overall the independent variables have a significant effect on consumer satisfaction. The t test results stated that product innovation, product quality and promotion had a positive and significant effect on consumer satisfaction, while product design and price had no significant effect.